Syntheses of Stable Isotope ［13C］/D Labelled p-Methoxybenzoic Acid - WANG Wei;DU Xiaoning;XU Jianfei;LEI Wen (Journal of Isotopes, 2020)
Stable isotope labelled p-methoxybenzoic acid is an important intermediate in the synthesis of stable isotope labelled preservative, anti-microbial, anti-fungal, spices, and other internal standard reagentsspices, drugs and other compounds. A new procedure for the synthesis of the ［13C］/D labelled p-methoxybenzoic acid has been developed in this paper. The stable isotope ［13C］/D labelled p-methoxybenzoic acid was synthesized from ethyl paraben and ［13C］/D labelled iodomethane (13CH3I or CD3I) under alkaline conditions via two steps. In this paper, the optimal reaction temperature, molar ratio, and reaction time were obtained by single factor experiment. The optimal reaction conditions were obtained as follows, the reaction temperature was 80 ℃, the molar ratio of ［13C］/D labelled iodomethane to ethyl paraben was 1.15∶1, the reaction time was 6 h. In the optimization conditions, the yield of ［13C］ labelled p-methoxybenzoic acid was 91.12%, and the utilization of 13CH3I was 79.32%. The melting point of product was 186.5~187.8 ℃. The product analyses were made with LC-MS, the chemical purity was 99.1%, and the isotopic abundance was 99.0 atom%13C. The qualitative analysis of product was confirmed by 1H NMR. By the same technological conditions, the stable isotope ［D］ labelled p-methoxybenzoic acid was synthesized from ethyl paraben and ［D］ labelled iodomethane (CD3I). The yield of ［D］ labelled p-methoxybenzoic acid was 90.49%, and the utilization of CD3I was 78.70%, and the melting point of product was 186.3~188.1 ℃. The product analyses were made with LC-MS, the chemical purity was 99.0%, and the isotopic abundance was 98.1 atom%D. The qualitative analysis of product was confirmed by 1H NMR.